2021
DOI: 10.3389/fendo.2021.795520
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Plasma FGF21 and Activated FGF21 Signaling in Visceral White Adipose Tissue and Improved Insulin Sensitivity in Gestational Diabetes Mellitus Subtype: A Case-Control Study

Abstract: ObjectiveTo study the discrepancy of the insulin sensitivity alteration pattern, circulating fibroblast growth factor (FGF21) levels and FGF21 signaling in visceral white adipose tissue (vWAT) of gestational diabetes mellitus (GDM) subtypes.Methods26 GDM women with either a predominant of insulin-secretion defect (GDM-dysfunction, n = 9) or insulin-sensitivity defect (GDM-resistance, n = 17) and 13 normal glucose tolerance (NGT) women scheduled for caesarean-section at term were studied. Blood and vWAT samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Next, we will continue to pay attention to such RCTs, and conduct further subgroup analyses of different GDM diagnoses. Finally, in combination with our previous studies (26,27,39), GDM subtypes should be considered as an important confounding factor that could affect the clinical efficacy of these oral hypoglycemic agents.…”
Section: Limitationmentioning
confidence: 79%
See 1 more Smart Citation
“…Next, we will continue to pay attention to such RCTs, and conduct further subgroup analyses of different GDM diagnoses. Finally, in combination with our previous studies (26,27,39), GDM subtypes should be considered as an important confounding factor that could affect the clinical efficacy of these oral hypoglycemic agents.…”
Section: Limitationmentioning
confidence: 79%
“…Metformin is regarded as an insulinsensitizing agent that is used as an oral hypoglycemic agent with limited power to control blood glucose levels during clinical practice (25). We have shown that there are three subtypes of GDM according to the heterogeneity in the physiological and pathological processes leading to hyperglycemia, which show different characteristics, risk factors, and insulin sensitivity alteration patterns (26,27). In the GDM-resistant subtype, metformin may improve blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments upregulated FGF21 levels, an effect previously observed after ethinylestradiol–cyproterone acetate-based OC treatment in PCOS adolescents ( 35 ). The inverse correlation between circulating FGF21 levels and visceral fat only in spiomet-treated girls could reflect an increase in FGF21 signaling in visceral adipose tissue, followed by a more insulin-sensitive status ( 40 ). No significant associations were found between the on-treatment FGF21 changes and ALT and GGT concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…There is also different information about the direction of this relationship. Some authors report that this relationship is positive [ 25 , 28 ] while others report that it is negative [ 29 ]. It can be explained by the fact that fasting blood glucose in diabetic patients has high variability, which can affect the correlation between glycemia and FGF21 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%